2018
DOI: 10.22456/1679-9216.16119
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and preliminary treatment of toxoplasmosis of pregnant goats in Kalubyia Gobernatore, Egypt

Abstract: Toxoplasmosis is a zoonotic disease that commonly infects goat in Egypt. For its diagnosis, sera form 48 pregnant does were tested for Toxoplasma gondii antibodies through indirect haemagglutination test (IHAT) and modified agglutination test (MAT). Samples were collected between the periods extended from November 2006 to March 2007. The seropositive rate of pregnant does (Meet Kenana, Kalubyia Governorate, Egypt) was 35.42% (17/48). After using MAT test against T. gondii-IgM, 11 sera (22.9%) were found positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
2
2
1
Order By: Relevance
“…The seroprevalence of T. gondii was higher in does (34.9%) than in bucks (33.3%) which has no statistically significant difference, similar results reported by (Xu et al, 2014). Regarding to aborted does in the present study, the seroprevalence of T. gondii was 62.8% higher than 35.4% and 22.9% by using IHA-IgG and MAT-IgM, respectively (Ramadan et al, 2007) and 17.1%by IHA-IgM (Mahboub et al, 2013). Furthermore, our study was lower than other reported in aborted does 80.0% by using DAT (Attia et al, 2017).…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 80%
“…The seroprevalence of T. gondii was higher in does (34.9%) than in bucks (33.3%) which has no statistically significant difference, similar results reported by (Xu et al, 2014). Regarding to aborted does in the present study, the seroprevalence of T. gondii was 62.8% higher than 35.4% and 22.9% by using IHA-IgG and MAT-IgM, respectively (Ramadan et al, 2007) and 17.1%by IHA-IgM (Mahboub et al, 2013). Furthermore, our study was lower than other reported in aborted does 80.0% by using DAT (Attia et al, 2017).…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 80%
“…Also the present results showed that the prevalence of T. gondii was higher in female (38&36%) than male (19& 19%) in younger goats (≤1.5 years) [37]. Such results may be attributed to prolonged exposure of olderly goats to infective T. gondiioocysts throughout their life [33].…”
Section: Discussionsupporting
confidence: 56%
“…The seroprevalence of T. gondii was higher in does (25.2%) than in bucks (13.3%) which has no statistically significant difference. Regarding to aborted does in the present study, the seroprevalence of T. gondii was 48.8% in our results higher than 35.4% by using (IHA-IgG) [7,23] and 17.1% by IHA-IgM (20). Furthermore, our study was lower than other reported in aborted does 80.0% by using Direct Antiglobulin test (DAT) [24].…”
Section: Discussioncontrasting
confidence: 70%